Application of electron microscopy methods to the study of porous and quartz-like glasses - Drozdova, Irina A.; Antropova, Tatiana V.; Tolkachev, Michail D. (Oficyna Wydawnicza Politechniki Wrocławskiej, 2005)
The structure of high-silica porous glasses and quartz-like (Vycor type) glasses has been investigated by transmission and scanning electron microscopy and by electron micro-probe analysis. Porous glasses (PGs) have been manufactured by acid leaching of phase-separated alkali borosilicate glass plates. To obtain the quartz-like glasses the PG samples were sintered at different temperatures up to 900°C. Before sintering a part of PGs was impregnated with salt solutions containing Ag. Features of the structure of quartz-like glass matrix are revealed. The parameters and arrangement of a photosensitive Ag-Hal phase in photochromic quartz-like glasses are determined.
Optica Applicata, Vol. 35, 2005, nr 4, s. 709-715
Keywords: optyka; porous glass; Vycor type glass; photochromic glass; electron microscopy; electron micro-probe analysis